1998
DOI: 10.1002/(sici)1097-4547(19981015)54:2<147::aid-jnr3>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Ran-2, a glial lineage marker, is a GPI-anchored form of ceruloplasmin

Abstract: Cell interactions in the nervous system are frequently mediated by surface proteins that are attached to the membrane by a glycosyl phosphatidylinositol (GPI) anchor. In this study, we have characterized the expression of such proteins on glial cells. We have detected a major GPI-anchored protein on astrocytes and Schwann cells, with a molecular weight of 140 kD. When Schwann cells were treated with forskolin to promote a myelinating phenotype, expression of this 140-kD protein dramatically decreased, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 55 publications
1
21
0
1
Order By: Relevance
“…A similar ferroxidase mechanism has also been proposed for the function of FET3 in iron uptake in yeast (28,29) and hephaestin in murine iron absorption (11). These two multicopper oxidases are membrane proteins, and recent studies have revealed a glycosyl-phosphatidylinositol-linked form of ceruloplasmin (30,31); however, additional experiments are needed to determine whether ceruloplasmin functions in solution or bound to the plasma membrane. The normal iron absorption in Cp Ϫ/Ϫ mice suggests that hephaestin is required for this process, consistent with the earlier observation of impaired iron transfer in copper-deficient animals.…”
mentioning
confidence: 76%
“…A similar ferroxidase mechanism has also been proposed for the function of FET3 in iron uptake in yeast (28,29) and hephaestin in murine iron absorption (11). These two multicopper oxidases are membrane proteins, and recent studies have revealed a glycosyl-phosphatidylinositol-linked form of ceruloplasmin (30,31); however, additional experiments are needed to determine whether ceruloplasmin functions in solution or bound to the plasma membrane. The normal iron absorption in Cp Ϫ/Ϫ mice suggests that hephaestin is required for this process, consistent with the earlier observation of impaired iron transfer in copper-deficient animals.…”
mentioning
confidence: 76%
“…Consistent with this concept, in patients with Wilson disease, the absence or dysfunction of a copper-transporting ATPase abrogates copper transfer into the secretory pathway, resulting in marked diminution in the serum concentration of ceruloplasmin (4). Extrahepatic synthesis of human ceruloplasmin has been detected in several tissues, including the retina and brain (5,6), and recent studies in rodents suggest that in brain and testis ceruloplasmin is synthesized as a glycosylphosphatidylinositol (GPI) 1 -anchored form via alternative RNA splicing (7)(8)(9)(10).…”
mentioning
confidence: 88%
“…This protein is synthesized and secreted by hepatocytes as a holoprotein with six atoms of copper tightly incorporated during its biosynthesis (2). In addition to the plasma form of ceruloplasmin, an alternative splice product yields a glycosyl phosphatidylinositol membrane-anchored form that is present in specific tissues (3)(4)(5)(6). Although copper has no effect on the rate of apoceruloplasmin synthesis or secretion (7), the plasma half-life of apoceruloplasmin is shorter than holoceruloplasmin and makes the serum concentration of this protein and the loss of oxidase activity a sensitive marker for copper deficiency (8,9).…”
mentioning
confidence: 99%